Analisis Opini Tidak Memberikan Pendapat BPK RI terhadap Laporan Keuangan Kabupaten Kepulauan Meranti - Monalika, Hani Putri (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This study aims to examine and analyze the Follow-up on the Audit Report of the Indonesian Supreme Audit Agency (BPK RI) on the Local Government Financial Report (LKPD) of the Kepulauan Meranti Regency, as well as to assess the level of transparency and accountability in financial performance reporting.Research methodology: This research uses a descriptive qualitative approach, employing document study or content analysis, and in-depth interviews with stakeholders such as auditors.Results: The audit opinion was a "disclaimer of opinion" due to several critical issues: the financial report lacked clarity and did not meet presentation standards, supporting documentation for financial transactions was insufficient, and the accounting system was inadequate, causing inconsistencies. Weak internal controls and limited resources, including insufficient training and experience in financial management, further contributed to the problem. The study recommends improvements in transparency, accuracy, and human resource capacity to achieve better audit opinions in the future.Conclusions: The 2023 BPK report highlights suboptimal management of Fixed Assets, affecting the quality of the financial statements. Follow-up actions have been delayed due to factors such as human resources, coordination, and weak internal control. Efforts should focus on improving asset management and coordination with BPK.Limitations: The limitations encountered during the research process include the difficulty in collecting confidential data and the challenges of conducting interviews with relevant decision-makers.Contribution: This study focuses more on qualitative research methods, which differentiates it from previous studies that have focused more on quantitative methods and statistical analysis.Keywords: Audit, BPK RI Audit Report, Financial Reporting, Follow-up, QualitativeHow to Cite: Monalika, H, P. (2024). Analisis Opini Tidak Memberikan Pendapat BPK RI terhadap Laporan Keuangan Kabupaten Kepulauan Meranti. Reviu Akuntansi, Manajemen, dan Bisnis (Rambis), 4(2), 265-273.